Successful Management of Extra Genital Transmissible Venereal Tumor in a Dog - Sumathi, Devaraju; Venkatesh, Atmakur; Sandhya Bhavani, Mohan; Selvaraj, Palaniswamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The canine transmissible venereal tumor (CTVT), also referred to as infectious sarcoma, venereal granuloma, transmissible lymphosarcoma, or sticker tumor, is a contagious neoplasm of unknown origin. It is sexually transmitted and naturally occurs only in dogs, primarily targeting the external genitalia of both male and female animals (Mukaratirwa and Gruys, 2003). Based on the location of the mass, the tumor is categorized into two types: genital TVT and extragenital TVT. The tumor commonly appears as ulcerated masses on the penis, prepuce, or vulva, which tend to bleed easily. Additionally, it may occur in other locations, such as the nasal cavity, oral cavity, eyes, and subcutaneous areas of the skin. Transmission among dogs and other canids can occur through coitus, licking, biting, or sniffing the affected areas (Das and Das, 2000; Rugmini et al., 2025). The neoplasia has a global distribution but is more prevalent in tropical and subtropical regions (Ferreira et al., 2000), particularly in countries with significant populations of stray dogs (Papazoglou et al., 2001). Asodiya et al. (2024), analysed 562 canine neoplasms recorded over 2017 to 2021 at Teaching Veterinary Clinical Complex, Anand (Gujarat, India), and recorded CTVT in 68 (12.09%) cases.